THE WAYS TO INCREASE THE EFFICIENCY OF DEKHAN AND HOUSEHOLD PLOTS - Muratovich, MukumovAbdugani; Yusuf Alikulovich, Usmanov; Sobir Boymirzayevich, Ruziboyev; Bakhrom Khamidovich, Majitov (International Journal of Psychosocial Rehabilitation, 2020)
The land use process in Deccan and household plots requires the creation of an effective and efficient mechanism. In this article, the mechanism for increasing the efficiency of their use is based on the analysis of dekhan and household plots.